2013
DOI: 10.2147/dmso.s51289
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic syndrome in hemodialysis patients as a risk factor for new-onset diabetes mellitus after renal transplant: a prospective observational study

Abstract: PurposeMetabolic syndrome is a cluster of biochemical abnormalities including cardiovascular and diabetes risk factors. The development of diabetes mellitus after renal transplant represents a major posttransplant complication that may adversely affect graft/patient survival. The aim of this study was to assess the role of metabolic syndrome in patients on hemodialysis as a risk factor for the incidence of new-onset diabetes mellitus after renal transplant.Patients and methodsThis was a prospective observation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 28 publications
2
8
1
Order By: Relevance
“…Metabolic syndrome prevalence among hemodialysis patients was 27.9% in Spain and Russia while similar results were reported by Perez and Radojica [8] [15]. In their studies, metabolic syndrome prevalence was respectively 29% and 29.8% in hemodialysis patients [8] and 34.3% [11] [16]. In UCAR study, metabolic syndrome prevalence based on IDF criteria was 36% [17].…”
Section: Metabolic Syndrome Prevalencesupporting
confidence: 72%
See 1 more Smart Citation
“…Metabolic syndrome prevalence among hemodialysis patients was 27.9% in Spain and Russia while similar results were reported by Perez and Radojica [8] [15]. In their studies, metabolic syndrome prevalence was respectively 29% and 29.8% in hemodialysis patients [8] and 34.3% [11] [16]. In UCAR study, metabolic syndrome prevalence based on IDF criteria was 36% [17].…”
Section: Metabolic Syndrome Prevalencesupporting
confidence: 72%
“…This prevalence within hemodialysis population may reach 70% [10]. Metabolic syndrome triples the risk of developing cardiovascular disease [9] [11], and increases two-fold mortality among hemodialysis patients [12].…”
Section: Introductionmentioning
confidence: 99%
“…Possible explanations for the discrepancies among these studies are differences in the study populations, inclusion criteria, dialysis method, confounding influences of covariates, and different retention of the various adiponectin isoforms in patients with residual kidney function. Interestingly, a recent study about metabolic syndrome in patients undergoing HD as a risk factor for new‐onset diabetes mellitus after renal transplant was reported . Therefore, further prospective investigations are required to confirm the role of metabolic disturbances in patients undergoing HD.…”
Section: Discussionmentioning
confidence: 99%
“…However, MetS and diabetes have been closely associated, both in the general population (13) and in dialysis patients. It has also been shown that the risk of post-transplant diabetes is associated with the presence of MetS in pre-transplantation (14).…”
Section: Introductionmentioning
confidence: 99%